Penatalaksanaan Pada Pedagang Perempuan Usia 55 Tahun Dengan Gout Artritis dan Dislipidemia Melalui Pendekatan Kedokteran Keluarga Di Wilayah Kerja Puskesmas Sukarame - catur ambar wati; Larasati, TA (CV. Jasa Sukses Abadi, 2024)
Gout arthritis is an increase in blood uric acid levels above normal which causes an inflammatory reaction in the joints. Prolonged gouty arthritis can damage the joints, soft tissues and kidneys. Dyslipidemia is a common metabolic condition characterized by a level of cholesterol in the plasma that exceeds normal values. Total cholesterol level is correlated as a strong risk factor for cardiovascular disease. Therefore, application of evidence-based medicine-based family doctor services to patients by identifying risk factors, clinical problems, and patient management based on a patient-centered and family problem-solving framework. so that treatment goals can be achieved, prevent complications that may occur, and improve the patient's quality of life. Primary data were obtained through history taking, physical examination and home visits. Secondary data were obtained from the patient's medical record. A Female patient, 55 years old, came with complaints of pain in both joints of the hands and feet and the back of the neck felt sore and tense. The patient has a history of high uric acid since the age of 36 years. In the knowledge assessment, the initial score before the intervention was 70 (patient), 50 (patient's family) and after the intervention became 100 (patient), 90 (patient's family). In terms of uric acid levels, uric acid levels decreased from 6.8 mg/dL to 6 mg/dL and blood cholesterol from 221 mg/dL to 188 mg/dL. In the aspect of diet there is a change in the type of food that is appropriate. In the aspect of physical activity there is a change in physical activity, sports 30 minutes 4 times a week. Enforcement of diagnosis and management of these patients has been done holistically, patient centered, family approach and community oriented based on several theories and the latest research. In the process of behavior change, the patient has reached the trial stage.